Communication Strategies, Theatrical Performances and Political Mobilization in Nigeria - Usiere, Akpan Udo; Akaenyi, Nkiruka Jacinta; Bassey, Bassey Esuk (Journal Integration of Social Studies and Business Development, 2025)
This study investigates the intersection of communication strategies and theatrical performances in the context of political mobilization in Nigeria. Anchored on Play Theory and Social Identity Theory, it examines how political parties engage the electorate through performative tactics during rallies. Utilizing an online survey method, data were collected from 600 respondents across four Nigerian states: Edo, Lagos, Kaduna, and Enugu. The findings reveal a dominant preference for musical performances (67%) over local comedies (24%) or cultural dances (2%), indicating a strategic shift toward celebrity-driven engagement. Moreover, 64% of respondents perceive these performances as propaganda rather than substantive political communication. These results suggest that theatrical strategies are widely used not merely to inform, but to entertain, emotionally charge, and shape group-based political identities. The study calls for a balanced integration of cultural authenticity and civic education in campaign performances to enhance democratic engagement and national cohesion.